Pilgrims’ Acceptance of Using Augmented Reality Applications While Performing The Hajj - Nassr, Rasheed; Saleh, Abdul aziz Hadi; Almalki, Hassan M.; Almalki, Sami; Musa, Shahrulniza (International Journal of Engineering and Technology, 2018)
The majority of pilgrims do not speak Arabic and may encounter difficulties performing Hajj in terms of appropriate procedures and places due to their unfamiliarity. Most pilgrims are there for the first time. Researchers and practitioners have sought to develop mobile-based applications to assist pilgrims in various tasks such as finding their way and avoid becoming lost, and to perform Hajj procedures properly based on guides on their mobiles. Among the developed applications, a few are based on augmented reality. Many remain in the research phase. However, the problem with many augmented-based applications developed for Hajj is the lack of user acceptance investigation before implementation. This study found that the applications developed for Hajj practices based on augmented reality lacked user acceptance test. This study proposes a model for user acceptance for mobile augmented reality applications developed for Hajj. It found that pilgrims’ motivations to use this type of application were ease of use and enjoyment, with little focus on its utility. This result is interpreted as meaning that the participants have yet to appreciate the utility of mobile augmented applications.